Commodifying Gender: A MatFem Perspective on "I Am For Sale, Who Will Buy Me?" - Zakia Resshid Ehsen Syeda (NUML Journal of Critical Inquiry)
This research investigates the commodification of women in Afghanistan through an in-depth analysis of the anonymous Afghani-authored short story, “I Am For Sale, Who Will Buy Me” (2010). Employing a Materialist Feminist lens and drawing upon Silvia Federici's theoretical framework in Caliban and the Witch (2004), the study examines the influence of religious doctrines on women's social and economic status, culminating in their marginalization. The analysis dissects the exploitation of gender roles, objectification of female bodies, and the commodification of Afghan women, revealing the intricate interplay between patriarchal systems, religious ideologies, and gender disparity. Additionally, the study explores historical and contemporary challenges faced by Afghan women, encompassing barriers to education, economic opportunities, and social integration. Emphasizing the necessity for comprehensive approaches, this research advocates transformative change and gender justice, stressing its urgency. Positioned within the broader discourse on women's struggles, this study aims to contribute an understanding of women’s oppression with a primary focus on fostering agency and societal transformation for Afghan women.